The Degrees of Separation in Turkish Cinema: The Sühely Eğriboz Number - Enes Abanoz (Erciyes İletişim Dergisi, 2020)
We live in a small-world where a person can reach another person via -on average- six steps by knowing a friend of a friend and with digitalization. One of the important questions in small-world research is about which node being in the center of the small- world. In here, with the central node definition, we refer to the node that can connect to all other nodes in the small-world by the shortest paths. In this study, we analyze the connection among actors/actresses of the Turkish Cinema and aim to define the center node in it. We use a graph analysis method that creates an Actor-Movie bipartite graph and projects it into a one-mode Actor-Actor graph to find the center node in the Turkish Cinema. Our results show that actor Sühely Eğriboz is the center node of Turkish Cinema graph with the lowest closeness centrality and average actor number value. Although there are paths that are longer than six steps, Sühely Eğriboz can reach any given actor/ actress with an average 3.142 steps.